Retskrivningsordbog på godt og ondt - Tarp, Sven (LexicoNordica, 2015)
This article analyses the new edition of Retskrivningsordbogen, the official Danish orthographic dictionary edited by the Danish Language Board. Although a dictionary of this type requires both language- political (incl. linguistic) and lexicographical knowledge, the analysis is made exclusively from the point of view of lexicography, with reference to a similar analysis of the previous edition (cf. Tarp 2002). It shows a number of improvements but also various problems. Finally, the article discusses the relation between the printed and the digital version of the dictionary and comes up with some proposals for the future.